Respuesta :
Solve for y, if x = 2
y = 5x + 3
Simply plug in "2" for "x" in our given equation :)
y = 5(2) + 3
Simplify.
y = 10 + 3
Simplify.
y = 13
To check our work, simply plug in 13 for y in the original equation, as well as plugging in 2 for x.
y = 5x + 3
13 = 5(2) + 3
Simplify.
13 = 10 + 3
Simplify.
13 = 13
Therefore, y = 13
~Hope I helped!~
y = 5x + 3
Simply plug in "2" for "x" in our given equation :)
y = 5(2) + 3
Simplify.
y = 10 + 3
Simplify.
y = 13
To check our work, simply plug in 13 for y in the original equation, as well as plugging in 2 for x.
y = 5x + 3
13 = 5(2) + 3
Simplify.
13 = 10 + 3
Simplify.
13 = 13
Therefore, y = 13
~Hope I helped!~